Urinary chemistry in healthy cross-bred pet rabbits ( Oryctolagus cuniculus ) and rabbits with suspected chronic kidney disease - Sze-Yu, Yeh; Chi-Hsuan, Sung; Pin-Chen, Liu; Ching-Fen, Wu; Tsai-Lu, Lin; Tsung-Li, Cheng; Chou, Chi-Chung (Translational animal science, 2025)
Renal biomarkers for early detection of decreased kidney function have been extensively studied in dogs and cats, but there is limited research for pet rabbits. Specifically, studies on urinary indices for cross-bred rabbits are scarce. Therefore, this study aimed to assess the potential use of urinalysis in cross-bred pet rabbits. Urine samples from 30 healthy crossbred pet rabbits and 11 rabbits with suspected kidney disease (KD) from three clinics were collected. RIs of urinary indices, including urinary protein, creatinine (uCRE), urinary protein-to-creatinine (UPC) ratio, gamma-glutamyl transferase (uGGT), and uGGT ratio, were established and compared to two published reference intervals (RIs). The results showed that healthy rabbits consistently had low urine protein levels and abnormal UPC ratios, compared to a published study involving only pure-bred rabbits. Rabbits with KD had higher urine protein levels and a significantly higher UPC ratio (P < 0.001), with 63% having ratios greater than 0.4. Additionally, rabbits with KD showed significantly (P < 0.001) lower uCRE levels and urine specific gravity (USG) with elevated uGGT index (P < 0.05), compared to the healthy group. Significant differences (P < 0.05) were also observed in urine color, turbidity, pH, and positivity of the occult blood by dipstick. This study underscores potential breed-specific variations in urinary protein levels and UPC ratio, as well as highlights the diagnostic potential of USG, UPC ratio, and uGGT index in rabbits with KD. However, the presence of breed-specific variations and technical nuances in laboratory equipment necessitate careful interpretation of results. Therefore, further studies across larger and more diverse rabbit populations are crucial to validate the diagnostic performance of urinary indices in diagnosing KD in rabbits.